A Novel Immune-Related ceRNA Network and Relative Potential Therapeutic Drug Prediction in ccRCC - Li, Weiquan; Meng, Xiangui; Yuan, Hongwei; Xiao, Wen; Zhang, Xiaoping (Frontiers in Genetics, 2022)
Renal cell carcinoma (RCC) is the third common solid tumor in the urinary system with a high distant metastasis rate. The five-year survival rate of RCC has reached 75% benefiting from the emergence and update of multiple treatments, while its pathogenesis and prognostic markers are still unclear. In this study, we committed to explore a prognostic ceRNA network that could participate in the development of RCC and had not been studied yet. We screened 9 immune-related hub genes (AGER, HAMP, LAT, LTB4R, NR3C2, SEMA3D, SEMA3G, SLC11A1 and VAV3) using data of The Cancer Genome Atlas Kidney Clear Cell Carcinoma database (TCGA-KIRC) through survival analysis and cox proportional hazard model. Next, we successfully constructed a ceRNA network of three mRNA (NR3C2 and VAV3), miRNA (has-miR-186-5p), and lncRNA (NNT-AS1) for ccRCC based on numerous online bioinformatics tools and cytoscape. Finally, we predicted five potential drugs (clemizole, pentolonium, dioxybenzone, Prestwick-691, and metoprolol) based on the above results.